PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN PENDEKATAN CONTEXTUAL TEACHINGAND LEARNING (CTL) - razali . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to determine the increase in student learning outcomes after applying Mathematics learning to numeracy operations material through the use of the Contextual Teaching and Learning (CTL) Approach for Grade IV students of SD Negeri 1 Panton Rayeuk T, East Aceh District. This type of research uses Classroom Action Research conducted in two cycles. The research subjects were grade IV students, amounting to 26 students. The results show that through the use of the Contextual Teaching and Learning (CTL) Approach, it turns out student learning outcomes increase in each cycle. Mastery of the material at the initial condition is still very low or has not worked well. Out of 26 students, only 15 students (33%) achieved the Minimum Mastery Criteria (KKM) which was set at 70 with an average value of 52. From the results of the research revealed that in cycle I the average value of students amounted to 69, learning completeness reached 58 %, the achievement of this value shows an increase in the value acquisition in the initial conditions. While in cycle II (the average value of students 78 and mastery learning reached 88%. The conclusion of this study was the use of Contextual Teaching and Learning (CTL) Approach in Mathematics learning of numerical operations material can have a positive effect on increasing student learning outcomes in class IV semester II of the academic year 2016-2017SD Negeri 1 Panton Rayeuk T East Aceh Regency.